1999
DOI: 10.1001/archotol.125.10.1083
|View full text |Cite
|
Sign up to set email alerts
|

Biochemoprevention for Dysplastic Lesions of the Upper Aerodigestive Tract

Abstract: Biochemoprevention is a promising biologic approach for laryngeal dysplasia and needs to be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 25 publications
2
77
0
2
Order By: Relevance
“…Many of these studies resulted in some degree of clinical success (6,7,(20)(21)(22)(23)(24). Critical evaluation of the clinical trials data, however, provides a strong rationale to evaluate other chemopreventive compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these studies resulted in some degree of clinical success (6,7,(20)(21)(22)(23)(24). Critical evaluation of the clinical trials data, however, provides a strong rationale to evaluate other chemopreventive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal cancer annually affects approximately 29,370 persons in the U.S., and more than 7,200 Americans die each year from this disease (1). Despite concerted efforts to improve treatments, 5 year survival rates for patients with advanced stage oral squamous cell carcinoma (oral SCC) remain among the lowest of solid cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 However, in a recent study using combinatorial treatment with 13-cis retinoic acid, interferon-α, and α-tocopherol in laryngeal dysplasia, histological response was not accompanied by reversal of the underlying genetic aberrations. 60 In clinically relevant doses, retinoids have tangible side effects, most notably mucocutaneous reactions, headache, xerophthalmia, and adverse alterations in lipid profiles.…”
Section: R E T R a C T E Dmentioning
confidence: 97%
“…Other chemopreventive agents that have shown preventive effects include selenium and vitamin E. Recently, Papadimitrakopoulou et al (12) reported that a combination of 13-cRA, vitamin E, and IFN-a restored advanced laryngeal premalignant lesions. Shin et al (13,14) showed that the same combination suppressed the development of second primary tumor and/or recurrence, and achieved an excellent survival rate in stage III/IV HNSCC, making this a promising combination chemopreventive approach.…”
Section: Chemoprevention For Hncmentioning
confidence: 99%